Effectiveness of Targeting Mechanisms Utilized in Social Protection Programs in Bolivia - Apella, Ignacio; Blanco, Gastón (World Bank, Washington, DC, 2015)
As part of the 2006-2011 National Development Plan, the Plurinational State of Bolivia launched two cash transfer programs and one youth labor training program aimed at promoting the accumulation of households’ human capital: the Juancito Pinto Educational Grant, the Juana Azurduy Mother-Child Grant, and my first decent job. The objective of this paper is to analyze the effectiveness of the targeting mechanisms utilized in these programs. Based on the information provided by the Ongoing Household Survey, we estimate the mechanisms’ potential inclusion and exclusion errors. The results permit us to suggest that the categorical selection mechanisms used in the three programs are effective in reaching the poorest population, although they present distinct levels of inclusion and exclusion errors associated with both the design and implementation problems of the particular mechanism utilized.